2017
DOI: 10.1016/j.jtho.2016.11.1858
|View full text |Cite
|
Sign up to set email alerts
|

P3.02c-063 Lactate Dehydrogenase (LDH) as a Surrogate Biomarker to Checkpoint-Inhibitors for Patient with Advanced Non–Small-Cell Lung Cancer (NSCLC)

Abstract: ratio [HR] 20.1, 95% confidence interval [CI] 5.5-73.9, p < 0.001), presence of liver metastasis (HR 5.5, 95% CI 2.1-14.6, p ¼ 0.001), and CNS metastasis (HR 2.9, 95% CI 1.1-7.4, p ¼ 0.027) were independent predictive factors for short PFS. Conclusion: Clinical factors including post-treatment NLR at 6 week might be predictive of clinical benefits from anti-PD-1 antibody therapy in lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The clinical utility of LDH lies in its prognostic ability. Our findings are consistent with earlier studies of pretreatment LDH as a prognostic marker in patients with advanced NSCLC treated with ICIs 13,14,22‐24 . In a meta‐analysis of retrospective studies of patients with NSCLC treated with ICIs, high pretreatment LDH was significantly associated with poor PFS and OS 14 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The clinical utility of LDH lies in its prognostic ability. Our findings are consistent with earlier studies of pretreatment LDH as a prognostic marker in patients with advanced NSCLC treated with ICIs 13,14,22‐24 . In a meta‐analysis of retrospective studies of patients with NSCLC treated with ICIs, high pretreatment LDH was significantly associated with poor PFS and OS 14 .…”
Section: Discussionsupporting
confidence: 91%
“…However, further research is required, as we do not advocate using on‐treatment LDH as a sole determinant for decisions around treatment cessation. Others have reported the potential value of combining the baseline and the relative change in LDH on treatment with C‐reactive protein, the neutrophil to lymphocyte ratio, and the tumor size to develop a risk score to predict radiological disease progression 24 . In particular, future studies could focus on validating pre‐ and on‐treatment LDH combined with other inflammatory and/or novel biomarkers such as circulating tumor DNA 26,27 as part of a risk tool using high‐quality and large data sets.…”
Section: Discussionmentioning
confidence: 99%
“…LDH has been found associated with poor prognosis when increased from 1 to 2.5 times ULN in patients treated with chemotherapy or targeted therapies . However, the effect of inflammatory status on benefit of ICI treatment in NSCLC patients is not well known yet, although some retrospective studies have shown that those with a high pretreatment of LDH level had a significantly shorter survival than those with normal LDH level …”
Section: Discussionmentioning
confidence: 99%
“…Finally, several exploratory studies provided a clue that baseline level of serum LDH may contribute to the identification of patients with NSCLC gaining better survival benefits from immunotherapy. Researchers evaluated the LDH level in 94 NSCLC patients treated with ICIs, and discovered that baseline LDH < 400 was related to improved OS (HR = 0.45, p = 0.01) (32). Further studies involving large-scale prospective cohorts may facilitate the progress in confirming the function of elevated LDH in NSCLC and its potential value in predicting efficacy.…”
Section: Routine Peripheral Blood Biomarkersmentioning
confidence: 99%